PENGGUNAAN MODIF (MODEL PEMBELAJARAN BERVARIATIF) DAN MEDAN (MEDIA PEMBELAJARAN) DALAM PEMBELAJARAN PPKN - NUNUNG FATIMAH (Universitas Tribhuwana Tunggadewi, 2020)
This study aims to analyze whether modif and medan can improve Civics learning outcomes class VII at MTs Negeri 2 Karanganyar. The method used was development research with a population of 315 students from 10 classes, with a random sample of 59 students. The results showed that the increase in Civics learning outcomes of students in the experimental class obtained a higher average pretest and psychological test compared to the control class, namely 80 and 65 and there was an implication on the increase in the value increase of pretest cycle I 79.3 (including good category) to 85.5 in the pretest cycle II and postest 95.9 cycle I to 98.6 (very good category) cycle II.